Identification of Bioactive Solutions of Corn Silk (Zea mays L.) Extract and Biological Activity Test By Bioinformatics - Afdhal Raihan; Angga Kurnia Illahi; Siti Rokhimah; Tasya Putri Pratama Elisa; Rita Maliza (Jurnal Biologi Tropis, 2023)
Corn silk (Zea mays L.) is an agricultural by-product that is discarded as agricultural waste. Corn silk has secondary metabolite compounds that have the potential to become useful bioactive compounds. The purpose of this study is to recognize the bioactive potential of corn hair through compound identification and biological activity. The method used is preparation and extraction by maceration method followed by identification of compounds through LC-MS analysis method and Phytochemical test, bioinformatic PASS test based on data through PubChem, ChemSpider, and way2drug web. The results obtained from corn silk have a group of active compounds, including alkaloids, flavonoids, saponins, steroids and triterpenoids. Analysis of potential bioactivity received Acaciin compounds have high antioxidant bioactivity with a Pa value of 0.815, 2-arachidonoylglycerol has high potential antiinflammatory bioactivity with a Pa value of 0.736 and 1,2-di-O-methyl-4-[(2R)-2,4-dihydro butyramide shows moderate possible antibacterial activity with a Pa value of 0.643. This study concludes that corn silk has high bioactive potential as an antioxidant, anti-inflammatory and antibacterial.